Spiritual philosophy of zakāt on achieving balanced economy - Busari, Saheed Abdullahi; Kazeem, Akeem Olayinka (Department of Qur'an and Sunnah Studies, AHAS KIRKHS, IIUM, 2024)
A holistic overview of Islamic dictates and principles shows that its injunctions have various practical implications for the improvement of human existence. All its basic ritual activities are directed toward the achievement of certain psycho-spiritual, sociopolitical, and economic goals. Every spiritual dictate in Islam is corroborated by sociopolitical or/and economic function(s). The five pillars of Islam have been variously re-interpreted based on the various verses of the Quran and hadiths to show how they represent frameworks that could inform continuous extrapolations of principles and guides on every aspect of human existence and endeavors. The consideration of Islamic principles and injunctions from these perspectives forms what the scholars termed as the higher objectives (maqāṣid) of Islamic law. For instance, ṣalāt, the most obvious rite that distinctively characterises the practical manifestation of Islamic spirituality, is categorically stated to be one of the ways through which a balanced moral and psychological disposition could be attained. Similarly, Hajj, the pilgrimage to Makkah, has been understood to represent an international sociopolitical platform where global issues could be effectively addressed